Cytotoxic Stilbenes and Derivatives as Promising Antimitotic Leads for Cancer Therapy - Faustino, Célia; Francisco, Ana P.; Isca, Vera M. S.; Duarte, Noélia (Current Pharmaceutical Design, 2018)
The growing incidence of cancer, the toxic side-effects associated with conventional chemotherapeutic agents and the development of multidrug resistance (MDR) drive the search for novel and more effective drugs with multi-target activity and selectivity towards cancer cells. Stilbenes are a group of naturally occurring phenolic compounds of plant origin derived from the phenylpropanoid pathway that may exist as cis- or trans-isomers. Although the trans-isomer is the more common and stable configuration, resveratrol being a representative compound, cis-stilbenes are potent cytotoxic agents that bind to and inhibit tubulin polymerization, destabilizing microtubules. This review summarizes the chemistry and biological evaluation of cytotoxic stilbenes and their synthetic derivatives as promising antimitotic leads for cancer therapy, focusing on the most potent compounds, the combretastatins. Combretastatins isolated from the South African bushwillow Combretum caffrum are among the most potent antimitotic and vascular disrupting agents (VDAs) of natural origin. Preclinical studies have demonstrated their potent antitumor effects in a wide variety of tumors, both in vitro and in vivo, being currently under evaluation in phase 2 and phase 3 clinical trials for several types of solid tumors. Topics covered herein include synthetic medicinal chemistry, modes of action, structure-activity relationships (SAR), preclinical and clinical studies as VDAs in cancer therapy, either as single agents or in combination with cytotoxic anticancer drugs, antiangiogenic agents, or radiation therapy, and development of appropriate formulations based on nanocarriers (e.g., liposomes, nanoemulsions, polymeric, lipid and ceramic nanoparticles, carbon nanotubes) for improved bioavailability and targeted delivery of combretastatins to the tumor vasculature.
Keywords: antimitotic